TRANSPLANTING MEDIATION INTO INDONESIAN CIVIL JUDICIAL SYSTEM - Riyanto Benny; Tunjung Hapsari; Nurul Dewi (Lembaga Penelitian Universitas Pasundan, 2017)
Mediation which has been integrated to court since 2003, was the result of transplantation from the United States of America with a low rate of success. If it is evaluated with the law of the non-transferable law by Robert B. Seidman, the rule of law derived from a country which is formed based on its socio-cultural condition cannot be automatically applied to a certain group of people living with a different socio-cultural awareness. The objective of the research is to find a suitable mediation concept to be applied in civil case litigation and to find out factors influencing the less-successful court connected mediation in Indonesia. This is a qualitative research using socio legal approach. Primary data obtained through interviews, secondary data obtained through document review. Based on qualitative analysis, it is found out that the suitable mediation concept applied in civil case litigation was repositioned as one of requirements to file a suit. Factors influencing less-successful court connected mediation in Indonesia are law and legislation, law enforcement officers, facilities and infrastructure, society and culture.